The Effect of Exogenous Sex Steroids on the Vaginal Microbiota: A Systematic Review - Ratten, Larissa K.; Plummer, Erica L.; Bradshaw, Catriona S.; Fairley, Christopher K.; Murray, Gerald L.; Garland, Suzanne M.; Bateson, Deborah; Tachedjian, Gilda; Masson, Lindi; Vodstrcil, Lenka A. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Exogenous sex steroids within hormonal contraception and menopausal hormone therapy (MHT) have been used for family planning and management of symptoms, without consideration of their effects on the vaginal microbiota. This is largely because their use predates our understanding of the importance of the vaginal microbiome on human health. We conducted a systematic review (PROSPERO: CRD42018107730) to determine the influence of exogenous sex steroids, stratified by oestrogen-containing or progestin-only types of contraception, and MHT on the vaginal microbiome, as measured by molecular sequencing methods. Methods: Embase, PubMed and Medline were searched for relevant literature published through to December 1st 2020. Eligible studies reported on the effect of specific exogenous sex steroids on the vaginal microbiome using a molecular method. Data regarding the ‘positive’, ‘negative’ or ‘neutral’ effect of each type of contraceptive or hormone therapy on the vaginal microbiome was extracted and summarised. A positive effect reflected a type of contraceptive/therapy that was associated with increased abundance of lactobacilli, a change to or maintenance of an optimal vaginal microbiota composition, or a decrease in bacterial diversity (specifically reflecting a low-diversity optimal microbiota state), relative to the control group. A contraceptive/hormone therapy was designated as having a negative effect on the vaginal microbiome if it resulted in opposing effects (i.e. loss of lactobacilli, a non-optimal microbiota state). When no significant change was found, this was considered neutral/inconclusive. Results: We identified 29 manuscripts reporting on the effect of exogenous sex steroids on the vaginal microbiome; 25 investigating hormonal contraceptives, and 4 investigating MHT. Oestrogen-containing contraception, particularly reflecting the combined oestrogen and progestin-containing contraceptive pill, had a positive effect on the composition of the vaginal microbiota. Progestin-only contraception, particularly reflecting depo-medroxyprogesterone acetate, had mixed effects on the microbiota. Among post-menopausal women using MHT, exogenous oestrogen applied topically was associated with increased prevalence of lactobacilli. Conclusion: Our findings suggest that oestrogen-containing compounds may promote an optimal vaginal microbiota, which could have clinical applications. The impact of progestin-only contraceptives on the vaginal microbiota is less clear; more data is needed to determine how progestin-only contraceptives contribute to adverse reproductive and sexual health outcomes.